How Do Gastroenterologists Assess Overall Activity of Eosinophilic Esophagitis in Adult Patients?. (March 2015) - Schoepfer, Alain M; Panczak, Radoslaw; Zwahlen, Marcel; Kuehni, Claudia E; Coslovsky, Michael; Maurer, Elisabeth; Haas, Nadine A; Alexander, Jeffrey A; Dellon, Evan S; Gonsalves, Nirmala; Hirano, Ikuo; Leung, John; et al.
Abstract : OBJECTIVES: There is no "gold standard" for assessing disease activity in patients with eosinophilic esophagitis (EoE). We aimed to compare physicians' judgment of EoE activity with patients' judgment of symptom severity. We also aimed to examine the relative contribution of symptoms as well as endoscopic and histologic findings in shaping physicians' judgment of EoE activity. METHODS: Six gastroenterologists (all EoE experts) assessed EoE‐associated symptoms in adult patients. Patients completed a symptom instrument and provided global assessment of EoE symptom severity (PatGA) (Likert scale: 0 (inactive) to 10 (most active)). Following esophagogastroduodenoscopy with biopsy sampling, gastroenterologists provided a global assessment of EoE activity (PhysGA) (Likert scale from 0 to 10) based on patient history and endoscopic and histologic findings. Linear regression and analysis of variance was used to quantify the extent to which variations in severity of EoE symptoms and endoscopic and histologic findings explain variations in PhysGA. RESULTS: A total of 149 EoE patients were prospectively included (71.8% male, median age at inclusion 38 years, 71.8% with concomitant allergies). A moderate positive correlation between PhysGA and PatGA (rho=0.442, P <0.001) was observed and the mean difference in the Bland–Altman plot was 1.77. Variations in severity of endoscopic findings, symptoms, and histologic findings alone explained 53%, 49%, and 30%, of the variability in PhysGA, respectively. Together, these findings explained 75% of variability in PhysGA. CONCLUSIONS: Gastroenterologists rate EoE activity mainly on the basis of endoscopic findings and symptoms and, to a lesser extent, on histologic findings.